2018
DOI: 10.1111/echo.14169
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular mechanics in adolescent and adult patients with a Fontan circulation: Relation to geometry and wall stress

Abstract: Background Patients with single ventricle physiology and Fontan circulation are at increased risk for late complications and reduced survival. The aim of the study was to investigate the correlation between ventricular geometry and systolic regional function in different underlying anatomic conditions in adolescent and adult Fontan‐palliated patients. Method In a retrospective cross‐sectional study, we measured 2D strain, ventricular diameters, ventricular volumes, ejection fraction (EF), global and segmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Therefore, inclusion of the septum in CMR strain measurements, as it has been reported up to now, will likely lead to arbitrary and inaccurate representation of ventricular systolic function. Strain analyses in patients with a functionally univentricular heart with inclusion of the hypoplastic ventricle has been described previously using echocardiography speckle tracking analysis [38], however, no direct comparison with the conventional "dominant ventricle only method" was provided.…”
Section: Dominant Ventriclementioning
confidence: 99%
“…Therefore, inclusion of the septum in CMR strain measurements, as it has been reported up to now, will likely lead to arbitrary and inaccurate representation of ventricular systolic function. Strain analyses in patients with a functionally univentricular heart with inclusion of the hypoplastic ventricle has been described previously using echocardiography speckle tracking analysis [38], however, no direct comparison with the conventional "dominant ventricle only method" was provided.…”
Section: Dominant Ventriclementioning
confidence: 99%
“…"Global strain" was defined as the average of peaksystolic strain-values of the six segments. Due to the lack of normal-values for HLHS patients, we defined hypokinesia according to previous strain-measurements in patients with Fontan-surgery, as peak longitudinal strain values > (weaker than) -8% as hypokinetic 24 . Based on previous studies on patients with transmural myocardial scar tissue values > (weaker than) -4% were defined as akinetic 25 .…”
Section: Assessment Of Segmental and Global Endocardial Longitudinal mentioning
confidence: 99%
“…The role of increased ventricular dyssynchrony inherently with Fontan patients that is conventionally measured by speckle-tracking echocardiography is increasingly recognized. It was reported that more than 15% of adult Fontan subjects suffered from classic pattern dyssynchrony (10). The ventricular dyssynchrony also varied among Fontan types, worse in AP Fontan in contrast to EC Fontan, probably due to the chronic severe reduction of ventricular preload in the AP Fontan subjects (11).…”
Section: Ventricular Dysfunctionmentioning
confidence: 98%
“…The ventricular dyssynchrony also varied among Fontan types, worse in AP Fontan in contrast to EC Fontan, probably due to the chronic severe reduction of ventricular preload in the AP Fontan subjects (11). Both increased ventricular electrical and mechanical dyssynchrony was in part associated with myocardial deformation, myocardial remodeling, and further ventricular systolic or diastolic dysfunction (10,12). Novel imaging modalities like CMR with feature tracking that enables reliable quantification of ventricular mechanics would be helpful to discover the interplay between ventricular dyssynchrony and ventricular dysfunction in Fontan patients.…”
Section: Ventricular Dysfunctionmentioning
confidence: 99%